2012
DOI: 10.1371/journal.pone.0045424
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of the Autonomous Nervous System in Patients with Temporomandibular Disorder: A Pupillometric Study

Abstract: The role of the autonomic nervous system (ANS) was recently investigated in Temporomandibular disorders (TMD). Several authors argue that in subjects with TMD there is a dysregulation of ANS. Recent literature support that Pupillometry is a simple non-invasive tool to study ANS. The aim of this study was to investigate the relationship between TMD and ANS activity using pupillometry recording in Infrared light at rest Mandible Position (RP); Infrared light at Forced Habitual Occlusion (FHO); Yellow-green light… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 43 publications
1
24
1
1
Order By: Relevance
“…11 The literature reveals that psychiatric disorders and psychosocial stress increase sAA secretion; 17,18 in addition, adults with TMD may reveal impairments in the sympathetic-adrenergic component of the autonomic system, which may influence pain symptoms and catecholamine responses at rest and during stress. 19,20 Each risk factor for TMD needs to be considered to appropriately diagnose and plan the management strategies. 1 Stress is considered as an important factor in the onset and maintenance of musculoskeletal disorders, although little is known about the relationship between TMD, stress, and anxiety in children.…”
mentioning
confidence: 99%
“…11 The literature reveals that psychiatric disorders and psychosocial stress increase sAA secretion; 17,18 in addition, adults with TMD may reveal impairments in the sympathetic-adrenergic component of the autonomic system, which may influence pain symptoms and catecholamine responses at rest and during stress. 19,20 Each risk factor for TMD needs to be considered to appropriately diagnose and plan the management strategies. 1 Stress is considered as an important factor in the onset and maintenance of musculoskeletal disorders, although little is known about the relationship between TMD, stress, and anxiety in children.…”
mentioning
confidence: 99%
“…Significant associations between compounds grouped by principal component analysis and obese asthma, current respiratory symptoms, obesity and body composition were also observed, even for low levels of EDCs exposure. Furthermore, our results showed that exposure to individual or combined EDCs is associated with changes in the ANS, specifically parasympathetic dysautonomia assessed through pupillometry, thus suggesting that EDCs may increase parasympathetic activity, resulting in a subsequent increase in the risk of asthma and obesity.…”
Section: Discussionmentioning
confidence: 68%
“…In their study, Manfredini et al [25] have shown that pain-related disability is strongly associated with depression and somatization. Other neurobiological mechanisms such as interference with endogenous regulator of the pain system, genetic factors as well as the disruption of the adrenergic function of the autonomic nervous system have also been put forward as contributing factors in the pathogenesis of CMD (Monaco et al [26]; Rinchuse and Kandasamy [27]).…”
Section: Resultsmentioning
confidence: 99%